Human Papilloma Virus Genotypes 16 and 18 among the South-Eastern Regional Bangladeshi Women - Siddiqui, Syeda Rumman Aktar; Rahman, Mohammad Zillur (Archives of Clinical and Biomedical Research, 2024)
Introduction: Cervical cancer ranks as the fourth most common cancer worldwide in terms of both incidence and mortality among women, accounting for 6.6% of all female cancer cases and 7.5% of cancer-related deaths in women. The primary cause of most cervical neoplasms, as well as other anogenital and oropharyngeal cancers, is infection by the human papillomavirus (HPV). Objective: This study aimed to determine the prevalence and distribution of HPV genotypes 16 and 18 among women in southeastern Bangladesh. Methods: This cross-sectional descriptive study was conducted at the Department of Laboratory Medicine in Epic Health Care Limited, Chattrogram, Bangladesh, from December 2023 to May 2024. The data were analyzed using Statistical Package for Social Sciences (SPSS) version 23.0. Descriptive statistical analyses were performed, and the results were presented in tables. Chi-square tests were applied to assess the relationship between age groups and the prevalence of specific HPV genotypes, with a significance level set at p<0.05. Results: A total of 284 study participants were enrolled, and cervical scrape samples were collected from all participants. However, 13 samples were unsuitable for PCR HPV detection, leaving 271 samples for HPV testing and genotyping for HPV 16 and 18. The most common age group among the participants was 31-40 years (121 women, 44.64%), with a mean age of 38.57 ± 8.93 years. HPV was detected in 10 cases, representing 3.69% of the study population. Genotype 16 was found in 3 women (1.10%) and genotype 18 in 1 woman (0.36%). Three cases of genotype 16 were detected in the 41-50 age group, while one case of genotype 18 was found in the 51-60 age group. No statistically significant association was observed between age groups and the prevalence of HPV genotypes 16 and 18 (P>0.05). Conclusion: This study offers valuable insights into the prevalence of HPV genotypes 16 and 18 among women in southeastern Bangladesh. Although these genotypes are recognized globally for their high risk of cervical cancer, the study found a relatively low prevalence (3.69%) among the women in this region. The study suggests enhancing public health initiatives, such as HPV screening and vaccination programs, to reduce the risk of cervical cancer in Bangladeshi women.